Guided-practice on occupational health and safety competencies of workers in the construction industry in Oyo State, Nigeria (2018)
Construction work and industry, although highly important to Nigeria's developmental processes, is characterized by high level of risks occurrence and hazards. This raises concern about the type of safety training provided in the industry and the instructional method used in imparting such safety trainings. A pretest-postest control group quasi experimental design was used for the study. The experimental group was exposed to guided-practice training method and lecture method was conducted on the control group. Two construction industries were purposively selected based on the criteria of workers' size, number of customers and experience of health risks. The workers in the two organizations who met the study's inclusion criteria were randomised into GpTM (11) and Lecture method (12) (Control) groups while treatment lasted eight weeks. Construction Industry Occupational Health and Safety Competencies Questionnaire (r= 0.85) and Occupational Health and Safety Competencies Scale (r=0.78) were used in collecting data for the study. Data analysis was done using ANCOVA at 0.05 level of significance. There was a significant main effect of treatment on the occupational health and safety competencies of workers (F(1.17)= 15.693. P<0.05, η2= .480).). There was no significant main effect of level of literacy on occupational health and safety competencies among participants (F(1.19) = . 659, p>0.05, η = . 034), but the two-way interaction effect treatments and literacy was significant. Guided-practice training method was significant in enhancing the occupational health and safety competencies of construction workers. The training method should therefore be employed regularly in safety trainings to achieve improved health and safety competencies in the Nigerian construction industry.